Combined experimental and computational study of the thermochemistry of methylpiperidines - da Silva, MAVR (2006)
To understand the influence of the methyl group in the stability and conformational behavior of the piperidine ring, the standard (p(0) = 0.1 MPa) molar enthalpies of formation of 1-methylpiperidine, 3-methylpiperidine, 4-methylpiperidine, 2,6-dimethylpiperidine, and 3,5-dimethylpiperidine, both in the liquid and in the gaseous states, were determined at the temperature of 298.15 K. The numerical values of the enthalpies of formation in the liquid and in the gaseous state are, respectively, -(95.9 +/- 1.6) and -(59.1 +/- 1.7) kJ, mol(-1) for 1-methylpiperidine; -(123.6 +/- 1.4) and -(79.2 +/- 1.6) kJ, mol(-1) for 3-methylpiperidine; -(123.5 +/- 1.5) and -(82.9 +/- 1.7) kJ, mol(-1) for 4-methylpiperidine; -(153.6 +/- 2.1) and -(111.2 +/- 2.2) kJ, mol(-1) for 2,6-dimethylpiperidine; and -(155.0 +/- 1.7) and -(105.9 +/- 1.8) kJ, mol(-1) for 3,5-dimethylpiperidine. In addition, and to be compared with the experimental results, theoretical calculations were carried out considering different ab initio and density functional theory based methods. The standard molar enthalpies of formation of the four isomers of methylpiperidine and of the 12 isomers of dimethylpiperidine have been computed. The G3MP2B3-derived numbers are in excellent agreement with experimental data, except in the case of 2,6-dimethylpiperidine for which a deviation of 9 kJ (.) mol(-1) was found. Surprisingly, the DFT methods fail in the prediction of these properties with the exception of the most approximated SVWN functional.